Echocardiographic assessment of left ventricular function - Zerbib, Yoann; Maizel, Julien; Slama, Michel (Journal of Emergency and Critical Care Medicine; Vol 3 (August 2019): Journal of Emergency and Critical Care Medicine, 2019)
Bedside echocardiography is a cornerstone tool in the management of critically ill patients with hemodynamic compromise. This technique should be considered not only as an imaging technique but as well as a hemodynamical method. Both transthoracic and transesophageal approach are used in intensive care unit (ICU) patients. Left ventricular (LV) systolic function can be assessed in daily clinical practice by measuring ejection fraction (EF) and cardiac output. But these indices are dependent on load conditions. Mitral anterior plane systolic excursion and tissue Doppler imaging (TDI) and speckle tracking by measuring the systolic motion velocity of the mitral annulus and the LV strain may together assess the true contractility of the left ventricle. dP/dt measured on mitral regurgitation flow could help to assess LV contractility. Maximal elastance was described to be the best parameter to evaluate myocardial systolic function but not available in daily practice at the bedside in ICU patients. LV diastolic function and pressure are useful to have a comprehensive evaluation of LV function and could be assessed by recording the mitral flow using pulsed Doppler and the early diastolic velocity of mitral annulus recorded using TDI. Echocardiography should be done in patients with shock to assess the pathophysiology of the shock and in pulmonary oedema to distinguish patients with cardiogenic oedema or acute respiratory distress syndrome (ARDS). Only echocardiography may assess the hemodynamic of patient with shock and/or respiratory failure and the only tool which permits to diagnose the cause of this hemodynamical failure.